Analisis Penagihan Pajak Pada Penerimaan Pajak Di Kantor Pelayanan Pajak Pratama Cilegon - Maulida Kusumawati; Mulyanah; Intan Puspanita; Selly Anggraeni Haryono (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
The purpose of this study is to find out and analyse the effectiveness and the tax contribution of tax collection to the tax revenues at KPP Pratama Cilegon. This study uses a descriptive method with data collection techniques in the form of interviews, observation, and documentation. The data analysis technique used is descriptive data analysis. The data that used of this study is the data of tax collection with the issuance process of warning letters, distress warrant and confiscation letter in 2021-2023 at KPP Pratama Cilegon. The results of this study find that tax collection at KPP Pratama Cilegon has been accordance with the applicable laws and regulations. The effectiveness of the tax collections for year 2021 and 2022 is classified as quite effective, while 2023 is classified as less effective. The contribution of tax collection to tax revenues at KPP Pratama Cilegon in 2021-2023 is very low. As recommendation to maximize the tax collection, KPP Pratama Cilegon needs to collaborate with other parties, conduct the socialization activities, increase the bailiff of state receivables, and strengthen the awareness of taxpayers regarding to tax avoidance.